ACER’s Global Logistics and Innovations: Total Costs Perspectives - Ming-Yuen Tarng; Po-Young Chu; Jau-Shin Hon (Asian Academy of Management Journal, 1998)
ACER’s Global Logistics and Innovations: Total Costs Perspectives (PDF not available)